2004
DOI: 10.1136/gut.2003.033563
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and vasoactive intestinal peptide antagonists attenuate rotavirus diarrhoea

Abstract: Background and aims: The mechanisms underlying intestinal secretion in rotavirus diarrhoea remain to be established. We previously reported that rotavirus evokes intestinal fluid and electrolyte secretion by activation of the enteric nervous system. We now report that antagonists for the 5-hydroxytryptamine 3 receptor (5-HT 3 ) and vasoactive intestinal peptide (VIP) receptor, but not antagonists for 5-hydroxytryptamine 4 receptor or the muscarinic receptor, attenuate rotavirus induced diarrhoea. Methods: Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 43 publications
6
52
2
2
Order By: Relevance
“…shown that drugs that inhibit the function of the ENS also could reduce symptoms of rotavirus disease in mice 75,76 .…”
Section: Results and Discussion Of The Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…shown that drugs that inhibit the function of the ENS also could reduce symptoms of rotavirus disease in mice 75,76 .…”
Section: Results and Discussion Of The Papersmentioning
confidence: 99%
“…VIP, 5--HT) and increase motility (e.g. 5--HT), rotavirus diarrhea was attenuated in mice pups 75 . Moreover, loperamide a drug acting on myenteric neurons, and atropine, acting on muscarinic acetylcholine receptors on nerves and enteric muscle cells, both attenuated diarrhea of infant mice 99 , further supporting the role of ENS in rotavirus diarrhea.…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase III trial, NK2 receptor antagonists reduced NKA-induced gut motility in healthy volunteers, but not the NKA-induced flush (49) that is probably mediated by NK1 receptors (50). Others have shown that SP receptor antagonists shortened the duration of diarrhea in mice (51).…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract provides the main route of access to the host for several viruses (Oberste et al 2000), including the human immunodeficiency virus (Smith et al 2003) and poliovirus (Mueller et al 2005), and for unconventional viruses or agents such as those involved in prion diseases (McBride et al 2001). These viruses can cause gastroenteritis, which is characterized by electrolyte and fluid secretion that seems to be triggered by local neural reflexes whose mechanism of activation is at present unknown (Morris and Estes 2001;Kordasti et al 2004). Some enteroviruses also show different degrees of neurotropism and neurovirulence that can lead to overt cytotoxic effects, latent infection, or viral spreading to the CNS (Irie et al 1989;Morrison et al 1991;Chen et al 2003;Holland-Cunz et al 2006;Selgrad et al 2009).…”
Section: Discussionmentioning
confidence: 99%